Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/min13070870
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of CSEM Exploration in the Brazilian Continental Margin

Abstract: The controlled source electromagnetic (CSEM) method is frequently used as a risk reduction tool in hydrocarbon exploration. This paper aims to provide a comprehensive historical review of the CSEM method’s twenty-year history in the Brazilian continental margin. Since 2003, we have significantly improved our understanding of CSEM resistivity data across various geological scenarios. This review presents a roadmap of the technical advancements in acquisition design and interpretation techniques. As a result, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…We also carried out comparisons with layering models between a 1D analytical solution and the 3D approximation solution to verify the correctness of the software. Since the relevant results have been published [ 31 , 43 , 44 , 45 ], the comparison is not shown here.…”
Section: Time-lapse Csem Data Modelingmentioning
confidence: 99%
“…We also carried out comparisons with layering models between a 1D analytical solution and the 3D approximation solution to verify the correctness of the software. Since the relevant results have been published [ 31 , 43 , 44 , 45 ], the comparison is not shown here.…”
Section: Time-lapse Csem Data Modelingmentioning
confidence: 99%
“…Menezes and coauthors [5] provide a comprehensive historical overview of the CSEM method in its 20-year usage in the Brazilian continental margin. The authors have shown progress in understanding CSEM resistivity data across various geological scenarios since 2003.…”
mentioning
confidence: 99%
“…Ultimately, Ref. [5] discuss potential upcoming CSEM applications in new energy resources and carbon capture and storage.…”
mentioning
confidence: 99%